Indoapseudes bamberi sp. nov. (Crustacea: Tanaidacea: Pagurapseudidae: Hodometricinae) from Iriomote Island, Ryukyu Islands, southwestern Japan - Kakui, Keiichi; Naruse, Tohru (Zootaxa, 2015)
We describe Indoapseudes bamberi sp. nov., based on a specimen from Funaura Bay, Iriomote Island, Japan. This species can be distinguished from its five congeners by having the combination of the antenna with a squama and pereopods 1 and 2 with one dorsal spine on the basis. We also determined part of the nucleotide sequence for the cytochrome c oxidase subunit I (COI) gene in I. bamberi, and present a key to Indoapseudes species.